Mt. Egmont - Taranaki: Zugleich ein Beitrag zum Studium der vertikalen Anordnung der Vegetation in Neuseeland - Schweinfurth, Ulrich (ERDKUNDE, 1962)
Even amongst the multitude of beautiful mountains in New Zealand Mt. Egmont is outstanding for its graceful appearance. The mountain occupies a unique position; resting - distinct from the other volcanoes - in splendid isolation and by virtue of that clearly visible from all sides, it juts forth into the Tasman Sea, exposed to all hardships and sudden changes the climate can provide in these latitudes. Needless to say, the mountain annually attracts a fair number of people, actually more than any other mountain in New Zealand, people, who only too frequently underestimate the difficulties the mountain offers. List of casualties on Mt. Egmont is the longest of any New Zealand mountain. Dr. Ernst Dieffenbach, German born naturalist of the New Zealand Company, was the first to reach the top of Mt. Egmont in 1839; many have followed since. In spite of the large number of visitors, literature on the mountain strangely enough is scanty and scientific information available might be called sufficient for the geologist only; botanists contributed bits and pieces here and there, but no comprehensive account of the vegetation of the mountain appeared so far. A reason for this doubtless is the difficult nature of the bush, though roads cut through the bush in N, E and SE to help the skiers to reach their playgrounds, offer reasonably good means of access to certain parts; the bush on both sides of the roads lines up as a solid wall. The present writer, while engaged in a survey covering most parts of New Zealand as well could not devote as much time to the mountain of Taranaki as he would have loved to do, indeed had to content himself to study the E and SE slopes from the boundaries of National Park to the summit, for which Mt. Egmont amongst a fair majority of rainy days presented one day out of the box. Special attention is paid to those types of vegetation, which the author regards to be peculiar on Mt. Egmont, as for instance the montane forest (goblin forest) from 800 to 1100 m. After presenting his material on Mt. Egmont the author reviews the vegetation of the mountain in comparison to the vegetation of the volcanoes to the East in the central parts of North Island, thereby briefly mentioning nearest habitats of Nothofagus E of Egmont, a genus entirely missing on the mountain; to the W the vegetation of the mountainous parts of Tasmania, where lifeforms com parable to those, which occur on Egmont, are met with, is cited. From this East-West review the author looks upon the vegetation of Mt. Egmont as occupying an especially interesting position, if one compares the forest vegetation of humid tropical mountains as studied by C. Troll, with forest vegetation in the Southern hemisphere, for which examples are quoted from the Tararuas (North Island, New Zealand), Fjordland (South Island) and Stewart Island. The study of the vegetation of Mt. Egmont, though of great interest in itself, appears to be one of special attraction in this greater context, in which Mt. Egmont occupies a unique place as it is - next to Ruapehu in central North Island - the last mountain towards N reaching the snow line, until in New Guinea we again find mountains, which provide the opportunity to study the various belts of vegetation from sea-level to snow line.